Cardiac troponin T: from diagnosis of myocardial infarction to cardiovascular risk prediction - Müller-Hennessen, Matthias; Vafaie, Mehrshad; Biener, Moritz; Giannitsis, Evangelos; Katus, Hugo (Circulation journal, 2013)
Cardiac troponins (cTns) T and I are exclusively expressed at high concentrations in cardiac muscle and have emerged as the preferred biomarker in the universal definition of myocardial infarction (MI). With the recent introduction of high-sensitivity (hs) assays, diagnostic sensitivity for earlier detection of MI has substantially improved. However, lowering the diagnostic cut-off has increased the detection of myocardial injuries in various non-acute coronary syndrome (ACS) conditions, which are not related to myocardial ischemia, leading to rising difficulties in diagnosing MI in clinical situations. Several approaches, such as serial sampling and incorporation of relative or absolute δ-changes, have been proposed to overcome the limitation of decreased sensitivity for MI diagnosis with hs-cTn assays. Current consensus for rapid rule-in proposes a 20% increase within 3 or 6h when baseline cTn levels are elevated. In the case of negative baseline values, relative increases ≥50% above the 99th percentile were found to be adequate to improve accuracy of MI diagnosis. Besides improved diagnostic accuracy for myocardial injury, even minor cTn elevations provide important prognostic information, and increased levels of cTn are associated with adverse outcomes in both the ACS and non-ACS condition, irrespective of whether the underlying cause is an acute or chronic illness. Thus, it is highly likely that lowering the diagnostic cut-off with even more sensitive assays might improve risk stratification in both conditions.  (Circ J 2013; 77: 1653-1661)
Gesehen am 22.06.2021